DIFFERENT DESTINATIONS OF DIFFERENT YOGA PRACTITIONERS (International Journal of Food and Nutritional Sciences, 2022)
There are different types of yoga. Karma Yoga, Jnana Yoga, Raj Yoga, Hatha Yoga, Astanga Yoga, Bhakti Yoga have been mentioned several times in Bhagavad Gita and other Indian Philosophical Systems. Bhardwaj (2019) says that whether they be karma yoga, bhakti yoga, jnana yoga or raja yoga, they pave the way for the lifting up of human consciousness to a higher and nobler realm of light, love and life with divine harmony and joy.The term “yoga ladder” is under explored in the academic world and otherwise. A lot of in-depth research has been done on yoga and different types of yoga but the term “yoga ladder” remains untapped.18 According to Prabhupada (1972) “The process of linking oneself with the Supreme is called yoga. It may be compared to a ladder for attaining the topmost spiritual realization. This ladder begins from the lowest material condition of the living entity and rises up to perfect self-realization in pure spiritual life. According to various elevations, different parts of the ladder are known by different names. But all in all, the complete ladder is called yoga and may be divided into three parts, namely Jnana-yoga, Dhyana-yoga and Bhakti-yoga.”